Utilization and Conservation Of Medicinal and Aromatic Plants: A Case Study from Mwdr, Nepal - Pokhrel, Kabi Prasad (Tribhuvan University Journal, 2010)
Mid Western Development Region (MWDR), a part of Nepali Himalayas, the globally significant and biologically diverse ecosystems, is remarkably rich in medicinal and aromatic plants, and other non-timber forest products (NTFPs). Government recorded data shows that about 700 species of herbal shrubs and NTFPs are found in the region and they are very important natural resources for human beings and for environmental balance. However, these vital and life supporting plants are in threats from deforestation, degradation, overuse and misuse. Unsustainable harvesting, improper storing, unfair trading, common property mismanagement, and policy environments have combined caused such valuable plants to vanish rapidly. The present paper based on empirical evidences points out that without people’s participation in resource development, conservation and management it is difficult to enhance the production of locally available resources on one hand, and not possible to reduce the rate of poverty and environmental deterioration on the other. Moreover, the findings of the study emphasize on the need of integrated conservation and development activities through watershed management in order to promote the sustainable livelihoods of people in the region.